Biomaterials and stem cells in regenerative medicine - Ramalingam, Murugan; Ramakrishna, Seeram; Best, Serena (Boca Raton, FL. : CRC Press, 2012)
'This book bridges the gap in experimental approaches and understanding among the key areas of biomedical research. It provides all-important aspects dealing with the basic science involved in structure and properties, techniques and technological innovations in processing and characterizations, and applications of biomaterials and stem cells in tissue regeneration. The coverage ranges from fundamental principles to current technological advancements in the major field of regenerative medicine at the macro/micro/nano/molecular scales. It includes breakthroughs in biomaterials, stem cells, tissue engineering, and drug delivery and the current perspectives of these key elements in the context of regenerative medicine'--
Includes bibliographical references and index.
Keywords: Biomedical materials; Stem cells -- Therapeutic use; Regenerative medicine -- Materials